Origin and epidemic status of porcine epidemic diarrhea virus variants in China. Issue 3 (16th December 2019) - Fan, Baochao; Jiao, Dian; Zhang, Ruoxi; Zhou, Jinzhu; Guo, Rongli; Yu, Zhengyu; Shi, Danyi; Zhao, Yongxiang; Gu, Jun; Niu, Beibei; Ma, Zengjun; Gao, Song; et al.
Abstract: From 2010, porcine epidemic diarrhea virus (PEDV) variants caused sequential outbreaks of disease in Asia and the United States. In this retrospective study, 49 complete spike (S) gene sequences were obtained from PEDV strains collected in China from 2014 to 2016. We observed that variant PEDV strains with novel insertions, deletions, and multiple S gene recombination types were present in China. In addition, mixed infections involving different variant strains were observed in some areas. Based on phylogenetic and recombination analyses, we determined that the newly emerged PEDV variants potentially originated via recombination between the earliest Chinese G1 genogroup strain, JS‐2004‐2 and earlier Korean pandemic strains. These findings provide important information for understanding ongoing PEDV outbreaks and suggest that novel variants make it more difficult to prevent PEDV infection.